Protective effects of Salvianic acid A against multiple-organ ischemia-reperfusion injury: a review - Yang, Shiyu; Chen, Heming; Su, Wei; Luo, Yunchun; Liao, Jun; Wang, Yun; Xiong, Liyan; Zhang, Chuan; Li, Fei; Chen, Zhe-Sheng; Wang, Tingfang (Frontiers in Pharmacology, 2023)
Ischemia-reperfusion (I/R) injury refers to a new injury caused by reperfusion after the restoration of ischemic tissue or organ blood supply. Salvianic acid A (danshensu) is a primary active ingredient extracted from Salvia miltiorrhiza. It has a protective function against I/R injury in the cardiovascular system, brain, liver, kidney, gastrointestinal tract, and other organs. This article reviews evidence of the protective effects of Salvianic acid A and its potential mechanisms of action in organ I/R injury protection. The aim of this review is to investigate the role of Salvianic acid A in the treatment of I/R injury, providing a reference resource that could facilitate subsequent studies.